KOTA BANDAR LAMPUNG DALAM PERSPEKTIF SEJARAH: DARI JEJAK KOLONIAL HINGGA ERA MODERN - Salsabila, Nitya; Ariana, Vilia; Sari, Juwita Permata; Imanita, Myristica; Rachmedita, Valensy (FKIP UNIVERSITAS LAMPUNG, 2024)
Bandar Lampung City is the capital city of Bandar Lampung province. This research aims to find out Bandar Lampung City in historical perspective from colonial traces to the modern era. The method used in this research uses the historical method, which consists of, criticism, interpretation, and finally historiography. The results of this study show that at first the Dutch succeeded in controlling the Lampung region and the indigenous people were only used as workers in their own territory, but over time the Lampung region, especially Bandar Lampung, could develop into a modern city. To become a modern city is certainly not an easy thing, many have to be sacrificed such as wealth and soul, but all have paid off in the current era which is now known as Bandar Lampung becoming a Modern City. In addition, the development of Bandar Lampung City continues to increase every year both in terms of population growth, education, and the economy.